How External Adaptation, Internal Integration, and Basic Assumptions Affect the Performance of Indonesian Palm Oil Companies (Jurnal Manajemen Bisnis, 2023)
The point of this study is to look into and try how organisational culture can be used to predict how well a palm oil company in Indonesia will do. It is a quantitative type of field study that is being used. Using purposive sampling, the population and group for this study were all managers of private oil palm plantation companies. There were 103 people in total, so 100 respondents were studied, and a Likert scale was used to measure them. The method for analysing the data uses both descriptive and proof analysis, along with the Partial Least Square (PLS) method and Smart PLS software. The study shows that external adaptation has a big and positive effect on how well people do their jobs. Adapting to changes outside the company has a positive and significant effect on its performance. On the other hand, integrating within the company does not have a positive and significant effect on overall work performance. and have a big impact on how well the company does, It is true that basic beliefs have a positive and significant effect on work performance, but they don't have any positive or significant effect on company performance. Additionally, work performance has a positive and significant effect on company performance.